Preliminary Experimental Evaluation of Buildability Improvement Methods for Concrete for 3D printing - Baldoceda, J.; Silva, G.; Kim, S.; Ruiz, G.; Pando, M.A.; Nakamatsu, J.; Aguilar, R. (Trans Tech Publications Ltd, 2023)
3D concrete printing is an innovative construction process based on fully autonomous material deposition. One of the challenges of implementing this technology is the development of printable concrete formulations, as this material must exhibit particular fresh-state properties. Among these, buildability is one of the most important. This property describes the material's ability to support weight at very early ages, allowing a layer-by-layer construction. Therefore, this paper aims to evaluate two approaches for improving concrete buildability: the optimization of the superplasticizer dosage and the external application of quick-setting admixture. The results showed that reducing superplasticizer content improved buildability by increasing the static yield strength. However, this approach has a collateral disadvantage as concretes presented problems during extrusion. On the other hand, the results of cylinder stability and Vicat tests indicate that the external application of quick-setting admixture leads to concretes with improved buildability without affecting the initial workability and a faster hardening process. According to these results, the latter approach can potentially be applied in small and large-scale 3D printing.
Keywords: Materials science; Superplasticizer; Vicat softening point; Hardening (computing); Extrusion; Composite material; Cement; Process engineering; Layer (electronics); Engineering; https://purl.org/pe-repo/ocde/ford#2.10.00